Effect of Changing Point Angle and Helix Angle Values of Drill Bit on Bone Drilling Simulation - Eko Wahyu Saputra; Mochammad Resha (Journal of Applied Science, Engineering and Technology, 2024)
Abstract: Orthopedic surgery treats disorders of the bones and soft tissues, especially in cases of accidental fractures. One method of fracture healing is to place plates and bolts in the bone. However, the drilling process for plate installation can cause an increase in temperature around the drilling area, which risks causing necrosis in the bone. This study aims to examine the effect of drill bit design on the temperature generated during bone drilling. Modifications to the point angle, helix angle of the drill bit can reduce the temperature during drilling. The results of this study suggest that optimizing the drill bit design can reduce the risk of necrosis and improve drilling efficiency, which can accelerate the healing process of broken bones. Keywords: Orthopedic surgery, bone fracture, drilling temperature, drill bit design, necrosis.